PENGARUH TEKANAN KETAATAN, PENGETAHUAN DAN PENGALAMAN AUDITOR TERHADAP AUDIT JUDGMENT DENGAN KOMPLEKSITAS TUGAS SEBAGAI VARIABEL MODERATING (Studi Empiris pada KAP Pekanbaru, Padang dan Medan) - Ayudia, Saydella; Hasan, Amir; Ilham, Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was aimed to examine the effect of obedience pressure, knowledge and experience of the auditor to audit judgment which is moderating by task complexity on the auditors who work in KAP Pekanbaru, Padang and Medan. This study used primary data by distributing questionnaires of 120 exemplar to the auditor who works at KAP Pekanbaru, Padang and Medan. Of these, questionnaires received back is 73 exemplar (60.8%). The questionnaire is not returned as much as 47 exemplar (39.2%) due to the existing questionnaires returned by respondents, so that questionnaires returned and can be processed is 73 exemplar 60.8%). Data collected were analyzed using multiple regression analysis and regression analysis with moderating variables. The results provide evidence that stress obedience, knowledge and experience of the auditor's effect on audit judgment at a significance level (α) of 5%. On the other hand, the complexity of the task to strengthen the influence of knowledge on audit judgment at a significance level (α) of 5%. However, the task complexity actually weaken the influence of pressure observance of audit judgment and weaken the effect of the experience of the auditors on audit judgment at a significance level (α) of 5%.Keywords: Obedience pressure, Knowledge, Experience Auditor, Audit Judgment and Task Complexity.